IMPLEMANTING INTERACTIVE LEARNING MODEL USING "GUESSING WORD GAME" METHODS AND ITS IMPACT TOWARD STUDENTS’ ENGLISH LANGUAGE LISTENING SKILLS at SMPN 2 AEK LEDONG - Utari, Richy Salwa; Arfanti, Yulia; Hasibuan, Ahmad Laut; Harianto, Harianto (PROJECT (Professional Journal of English Education), 2024)
Acquiring the skill of listening to and comprehending spoken language is one of the first steps towards acquiring a language. The next stage is to follow along, get into the habit, and use it in daily life. Since reading and listening need the understanding of language without the production of it, they are regarded as receptive abilities. These abilities require the ability to absorb and understand linguistic input. One way that helps improve pupils' speaking and listening abilities is the word-guessing method. This approach encourages dialogue, which is ideal for developing speaking abilities during the educational process. Students can improve their speaking skills by actively participating in it and being engaged.The purpose of this study was to determine the efficacy of this approach.